Liar's poker : rising through the wreckage on Wall Street - Lewis, Michael (Michael M.) (New York : W.W. Norton, 2010)
The author recounts his experiences on the lucrative Wall Street bond market of the 1980s, where young traders made millions in a very short time, in a humorous account of greed and epic folly.
Liar's poker -- Never mention money -- Learning to love your corporate culture -- Adult education -- A brotherhood of hoods -- The fat men and their marvelous money machine -- The Salomon diet -- From geek to man -- The art of war -- How can we make you happier? -- When bad things happen to rich people.
B003E20ZRY (Amazon Standard Identification Number (ASIN)).
BBS
System requirements vary by file format. See OverDrive download page for details.
Keywords: Lewis, Michael; Lewis, Michael; Salomon Brothers; Salomon Brothers; Brokers -- United States -- Biography; Bonds -- United States; Business & finance; Bonds; Brokers; United States